Proverbs and Sayings in Hafiz' Verses - Ghulam Akbar; Muhammad Waseem (بازیافت, 2018)
Hafiz was a Persian poet who lauded the joys of love and wine but also targeted religious hypocrisy. His collected works are regarded as a pinnacle of persian literature and are often found in the homes of people in the persian speaking world who learn his poems by heart and still use them as proverbs and sayings. Themes of his ghazals are the beloved, faith and exposing hypocrisy. In his ghazals, he deals with love wine and tavern, all presenting the ecastasy and freedom from restraint whether in actual wordly release or in the voice of the lover speaking of divine love.